Performance-based blast resistant design of reinforced concrete frame structures under distant explosions - Rong, Haicheng (2008)
Numerical finite element analyses to evaluate the structural dynamic responses are performed on a six-storey reinforced concrete frame structure under distant explosion conditions. To keep the localized responses of the blast-loaded members under control in meeting the expected performance level, a performance-based blast resistant design approach for reinforced concrete structural members is developed by using energy spectra. The accuracy of the approach in terms of controlling the responses of the designed member under the given blast loading is numerically evaluated by comparing them with their respective design targets. In addition, a new design method is presented for a multi-storey reinforced concrete frame structural system based on the equivalent static force (ESF) to ensure the global responses in terms of maximum inter-storey drift ratio (MIDR) at the expected global performance level. The implementation of the design method is demonstrated from practical design examples and followed by the numerical verification study